Teaching English as a Glocalized Communication (TEGCOM): Some Empirical Examples / Ribut Wahyudi - Wahyudi, Ribut (Universiti Teknologi MARA, Kedah, 2016)
The purpose of this article is to discuss my own auto ethnographical reflection of teaching experiences obtained during a 6 month Discourse Analysis course back in 2013. I will discuss my teaching experiences in relation to the TEGCOM and its related literatures. I then showcase what and how my teaching experience matches with the pedagogy. I use the following TEGCOM (Lin, Wang, Akamatsu & Riazi (2002; 2005) reference to contextualize the Western materials to students’ cultural contexts. In this paper, I use auto-ethnography (Cauley, 2008; Ellis, Adam, Bochner, 2011) in elaborating my experience of teaching Discourse Analysis course, an empowering methodology which allows the personal story through the use of pronoun “I” (Dyson, 2007).